2014
DOI: 10.1111/sltb.12100
|View full text |Cite
|
Sign up to set email alerts
|

Grief and Attitudes Toward Suicide in Peers Affected by a Cluster of Suicides as Adolescents

Abstract: Eighty-five young adults exposed to a cluster of peer suicides as adolescents completed measures of attitudes toward suicide, grief, and social support. Closeness to the peers lost to suicide was positively correlated with grief and the belief that suicide is not preventable, with grief further elevated in close individuals with high social support from friends. Overall, social support was related to healthy attitudes about suicide including preventability, yet it was also related to some stigmatizing beliefs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Twenty-one studies from the same research group are marked with °. Grief was expressed in thoughts and feelings and affected behavior and relationships (Abbott & Zakriski, 2014;Bartik, Maple, Edwards, & Kiernan, 2013a;Cerel, Fristad, Weller, & Weller, 1999;Dyregrov & Dyregrov, 2005;Hoffmann, Myburgh, & Poggenpoel, 2010;Ratnarajah & Schofield, 2008;Silvén Hagström, 2013). Adolescents reported a variety of feelings, including guilt, blaming (others and self), shame, anger, rejection, and perceived stigma; and adolescents engaged in risky coping behaviors such as increased alcohol consumption (Bartik et al, 2013a;Hoffmann et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies from the same research group are marked with °. Grief was expressed in thoughts and feelings and affected behavior and relationships (Abbott & Zakriski, 2014;Bartik, Maple, Edwards, & Kiernan, 2013a;Cerel, Fristad, Weller, & Weller, 1999;Dyregrov & Dyregrov, 2005;Hoffmann, Myburgh, & Poggenpoel, 2010;Ratnarajah & Schofield, 2008;Silvén Hagström, 2013). Adolescents reported a variety of feelings, including guilt, blaming (others and self), shame, anger, rejection, and perceived stigma; and adolescents engaged in risky coping behaviors such as increased alcohol consumption (Bartik et al, 2013a;Hoffmann et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This must be interpreted in the context of the greater tolerance of suicide in Japanese culture [ 42 ]. In a US study 85 young adults exposed to a peer suicide cluster in adolescence were more likely than 67 unexposed controls to normalise suicide but also more likely to find it incomprehensible [ 40 ]. Those who rated themselves as close to the deceased were more likely to identify with the attitudes “People often die by suicide on a whim”, and “If people want to die by suicide, we can’t stop them” [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a US study 85 young adults exposed to a peer suicide cluster in adolescence were more likely than 67 unexposed controls to normalise suicide but also more likely to find it incomprehensible [ 40 ]. Those who rated themselves as close to the deceased were more likely to identify with the attitudes “People often die by suicide on a whim”, and “If people want to die by suicide, we can’t stop them” [ 40 ]. A study of 54 workers in a US suicide intervention centre found that they had a greater fear of death than 62 psychology student controls, but such fears were not specific to suicide [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A huge majority (93.4%) are of the strong opinion of communicating psychological problems& hence of seeking help as shown in Table 3 [9,10] Tarun Mene et al in an Indian study from Arunachal Pradesh, Peltzer, Cherian et al 2000,Eshun et al 2003demonstrated that acceptable or positive ATTS were often found prior to suicidal ideation/behaviour. [11,12,13] According to Eskin [14][15][16][17][18] Upon further categorization of attitude towards suicide data into male & female sets, as depicted in Table 3 [19,20] When it comes to attitude towards a suicidal person, our medical students have a very high acceptance score and also are ready to help them as evident in Table 2. But they are not fully agreeable to a suicidal person disclosing their ideas or plans about suicide with higher variation.…”
Section: Discussionmentioning
confidence: 99%